2014
DOI: 10.1017/s1751731113002103
|View full text |Cite
|
Sign up to set email alerts
|

Methods for assessing phosphorus overfeeding on organic and conventional dairy farms

Abstract: Phosphorus (P) losses from dairy farms can severely damage aquatic ecosystems, so it is important to have tools to assess overfeeding of P. This study screened P intake and faecal excretion of different P fractions in dairy cows on conventional and organic farms, compared the P feeding level of the herds against the recommendations and analysed different sampling and analysis methods for assessing the general status of P feeding on the farms. The organic (n = 14) and conventional farms (n = 15) were of compara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…AEP is an appropriate indicator of P overfeeding since surplus P consumed is almost entirely excreted as acid soluble P . However, when it comes to the assessment of P overfeeding it was suggested that TP might be a more attractive alternative since the cost of analysis is lower and the handling of the samples is less complicated . Their suggestion is confirmed by the present results, since AEP was reflected by TP, and TP was slightly stronger related to P intake.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…AEP is an appropriate indicator of P overfeeding since surplus P consumed is almost entirely excreted as acid soluble P . However, when it comes to the assessment of P overfeeding it was suggested that TP might be a more attractive alternative since the cost of analysis is lower and the handling of the samples is less complicated . Their suggestion is confirmed by the present results, since AEP was reflected by TP, and TP was slightly stronger related to P intake.…”
Section: Resultssupporting
confidence: 73%
“…Furthermore, the rapidly depleting rock P reserves require a more equitable management of this essential and non‐renewable resource . Dairy cows in North America and Europe are often fed P in excess of their requirement . More than two‐thirds of the P consumed by cattle is generally excreted in manure, mainly as soluble inorganic P .…”
Section: Introductionmentioning
confidence: 99%
“…The potential for N and P to be environmental contaminants [44,45] resulted in more studies quantifying intake and excretion of these nutrients on commercial dairy farms compared with K, S, Ca and Mg. For instance, mean dietary P (4.5 g P/kg DM) of grazing herds on these study farms was greater and the ranges generally wider than Spanish (3.98, 2.8 to 5.4 g/kg DMg) [22], Swedish ([3.7, 2.1 to 5.2 g/kg DM) [46], northeast US (4.42, 3.6 to 7.0 g/kg DM) [9], and Wisconsin ([4.0, 2.3 to 8.5 g/kg DM) [47] commercial farms, and well in excess of NRC [35] recommendations of 3.2 to 3.8 g/kg DM for cows producing 22 to 55 kg milk/day. Mean P concentration of dietary components (0.47%, 0.01 to 3.99%) provided to the cows in this study was less than for Swedish rations (0.6%, 0.25 to 1.1%) [46], and Wisconsin (1..8%, 0.24 to 3.58%) [47]), and closer to that of Idaho (0.49%, 0.41 to 0.50%) [19]) farms. Arriaga et al [22] attributed high P intakes in their study mainly to grass silage, although concentrates had higher P concentrations.…”
Section: Nutrient Intakesmentioning
confidence: 81%
“…However, the cost-effective solution to the challenge of managing P-rich manure remains the minimising of P feeding because in areas with a high soil P index, farmers may incur additional costs for the transportation of manure to further lands (Knowlton, 2011). However, encouraging manure P analysis remains important for minimising P feeding because it provides farmers with an indication of the relative degree of excess P feeding on their farms (Nordqvist et al, 2013). In the current study, farmers of smaller herds were less likely to analyse their manure P than larger herds.…”
Section: Factors Influencing Farmers' Awareness Of Phosphorus Polluti...mentioning
confidence: 67%